Analisis dan Pemodelan Sistem Informasi pengelolaan Persediaan Barang (Studi Kasus Bagian Sarana dan Prasarana UB Press) - Era Nurria; Aditya Rachmadi; Ismiarta Aknuranda (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
UB Press is part of UB's academic implementation support unit (UKPPA) with main program focus on e-book, conventional and citation. UB Press is divided into three divisions, publishing, marketing and administration, finance & facilities and infrastructure. The process of activities at facilities and infrastructure division still use conventional processes of demand for goods, data collection of goods and goods out and ordering goods all still using manual form. Given these issues information system that can support the business process of goods management is required. The model of management information system using Rational Unified Process which focus in the inception and elaboration phases. In the inception phase, need to analyze is performed which produces 15 features consisting of 12 functional requirements and 3 non-functional requirements and 12 use cases. In the elaboration phase needs to modeling the system and evaluate the system. At the modeling phase the system produces analysis of classes to be a class diagram, data modeling and user interfaces modeling. In the evaluation phase the system uses a traceability matrix where each condition can be traced to features, use cases, sequence diagrams, activity diagrams and interfaces. In addition to using traceability matrix, a consistency analysis was used to calculate the consistency level of need indicating 100 % shows all of the needs element are connected.